Sanctions law - Gordon, R. J. F. (Richard John Francis); Smyth, Michael; Cornell, Tom (Lawyer) (Hart Publishing, 2019)
"The aim of the book is to create a user-friendly, accessible guide to the complex area of sanctions law. In particular, the book will examine how sanctions restrictions work in practice, and what the implications are for multinational businesses operating across numerous sanctions regimes. To this extent, the book will consider the interrelationship between sanctions at the supranational and national levels, including the impact of the far-reaching US sanctions regime. The book's aim is not to provide an exhaustive list of sanctions regulations, but rather a comprehensive framework for engaging with the relevant legislation and the main issues arising there from. Reinforcing this practical and commercially-focused approach, each chapter is written in a format that enables easy reading and rapid assimilation. The most relevant materials be they legislative or case-law are outlined at the start of each chapter. In addition the chapter will include a section with key principles, providing the clearest possible treatment of the subject"--